Stackable pallet-shaped triboelectric nanogenerator for water wave energy harvesting - Yang, Tong Jun; Soong, Lim Way; Chin, Yeo Boon; Chin, Calven; Wai, Liew Kia; Pocherd, Pee; Wiwatcharagoses, Nophadon (Edelweiss Applied Science and Technology, 2025)
Water wave energy is a vast and underutilized renewable resource. It has the potential to power distributed devices in marine environments. Triboelectric nanogenerators (TENGs) have emerged as a reliable technology for harvesting low-frequency and irregular mechanical energy from natural sources like ocean waves. Herein, a stackable pallet-shaped triboelectric nanogenerator (SP-TENG) is proposed for water wave energy harvesting. The SP-TENG is based on a stackable pallet-inspired structure, offering a modular and scalable platform for converting low-frequency motion into usable electrical energy. By utilizing the solid-solid freestanding triboelectric layer mode, the SP-TENG is able to generate electricity through periodic contact and separation between triboelectric materials. In this paper, two different types of SP-TENGs are designed and tested, each using different triboelectric material configurations in the sliding components. Polytetrafluoroethylene (PTFE) and aluminum were chosen for their strong triboelectric polarity difference, which enables efficient charge generation. One prototype uses solid PTFE plates, while the other uses aluminum-coated sliding components. The main goal is to compare their performance in energy generation under simulated wave conditions. All experiments were conducted using manual sliding motion at approximately 1 Hz to mimic low-frequency wave excitation. The maximum voltage achieved by the best-performing SP-TENG is 4 V. An SP-TENG is able to power 93 LEDs as well as other small electronic devices. Therefore, the SP-TENG is proven to be an effective solution for harvesting water wave energy and powering various marine applications in the future.